Sistem Monitoring KWH Meter berbasis Modul Komunikasi LoRa - Muhammad Isman Suga; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Electricity is one of the necessities of human life. One of those that provide electricity services in Indonesia is a state-owned company, namely PLN. PLN itself has 2 categories of electricity customers, namely, prepaid and postpaid. Postpaid customers make bill payments according to the energy used for a period of 1 month. However, in reality in the field, according to the head of the daily management of YLKI (Indonesian Consumers Foundation), Tulus Abadi, PLN officials frequently record errors for postpaid customer electricity meters. The problem is that PLN is still monitoring customers manually for postpaid electricity. To overcome this, it is necessary to establish a kwh meter monitoring system for PLN customers. This monitoring system will send KWH usage data using the LoRa communication protocol which will then be sent through the gateway, then the data will be forwarded to the broker using the MQTT protocol and the data will be subscribed to by the client so that the data can be monitored regularly. In the research conducted, the author of this monitoring system has an average percentage of error data kwh of 0% and a wattage of 0.6% compared to other sensors KWE-PM01. For sending data from the sensor node to the client it can run well. At a distance of 100 meters to 300 meters, sending from the sensor node to the gateway is the best delivery in this study. Because the successful rate for testing single and multiple nodes at this distance, the packet can be received 100% by the gateway.